Dynamics of the soil microbial community associated with Morchella cultivation: diversity, assembly mechanism and yield prediction - Yue, Yihong; Hao, Haibo; Wang, Qian; Xiao, Tingting; Zhang, Yuchen; Chen, Qun; Chen, Hui; Zhang, Jinjing (Frontiers in Microbiology, 2024)
Introduction The artificial cultivation of morels has been a global research focus owing to production variability. Understanding the microbial ecology in cultivated soil is essential to increase morel yield and alleviate pathogen harm. Methods A total of nine Morchella cultivation experiments in four soil field types, forest, paddy, greenhouse, and orchard in Shanghai city were performed to determine the potential ecological relationship between Morchella growth and soil microbial ecology. Results Generally, significant variation was observed in the soil microbial diversity and composition between the different experimental field types. The niche width analysis indicated that the bacterial habitat niche breadth was significantly greater than the fungal community width, which was further confirmed by a null model that revealed that homogeneous selection could explain 46.26 and 53.64% of the variance in the bacterial and fungal assemblies, respectively. Moreover, the neutral community model revealed that stochastic processes dominate the bacterial community in forests and paddies and both the bacterial and fungal communities in orchard crops, whereas deterministic processes mostly govern the fungal community in forests and paddies and both the bacterial and the fungal communities in greenhouses. Furthermore, co-occurrence patterns were constructed, and the results demonstrated that the dynamics of the soil microbial community are related to fluctuations in soil physicochemical characteristics, especially soil potassium. Importantly, structural equation modeling further demonstrated that the experimental soil type significantly affects the potassium content of the soil, which can directly or indirectly promote Morchella yield by inhibiting soil fungal richness. Discussion This was the first study to predict morel yield through soil potassium fertilizer and soil fungal community richness, which provides new insights into deciphering the importance of microbial ecology in morel agroecosystems.